Pola Implementasi Gerakan Literasi Sekolah Di SMP Negeri 5 Malang - Syaiful Rahman; Akhsanul In'am (Jurnal Kebijakan dan Pengembangan Pendidikan, 2020)
Abstract: The students 'reading ability is low, it certainly affects the students' writing ability. Implementation of the School Literacy Movement is a solution to students' low reading ability. This study aims to describe the pattern of Implementation of School Literacy Movement that took place in SMP Negeri 5 Malang. This study uses a qualitative approach with a descriptive type that describes the School Literacy Movement in SMP Negeri 5 Malang. Data collection techniques using observation, interviews, and documentation. The results showed that the pattern of implementation of school literacy measures in SMP Negeri 5 Malang included: 1) The habituation phase was carried out by way of students bringing reading books from home or borrowing books to the library. At this stage a class reading corner was prepared, reading 15 minutes before learning began, and a literacy journal; 2) The Development and Learning Phase increases the school resources especially at the State Junior High School 5 Malang, namely the existence of a reading corner in each class, an increase in the number of books, a 30-minute reading club, and a product of the School Literacy Movement.Keywords: School Literacy Movement, Habituation Phase, Development Phase, LearningAbstrak: Kemampuan membaca peserta didik tergolong rendah pasti berpengaruh terhadap kemampuan menulis peserta didik. Implementasi Gerakan Literasi Sekolah menjadi solusi atas kemampuan membaca siswa yang rendah.  Penelitian ini bertujuan untuk mendeskripsikan pola Implementasi Gerakan Literasi Sekolah yang berlangsung di SMP Negeri 5 Malang. Penelitian ini menggunakan pendekatan kualitatif dengan jenis deskriptif yang mendeksripsikan Gerakan Literasi Sekolah di SMP Negeri 5 Malang. Teknik pengumpulan data menggunakan observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukan bahwa pola implementasi geakan literasi sekolah di SMP Negeri 5 Malang meliputi: 1) Tahap Pembiasaan dilaksanakan dengan cara peserta didik membawa buku bacaan dari rumah atau meminjam buku ke perpustakaan. Pada tahap ini sudah disiapkan pojok baca kelas, membaca 15 menit sebelum pembelajaran dimulai, dan jurnal literas; 2) Tahap Pengembangan dan Pembelajaran meningkatkan sumber daya sekolah khusnya di Sekolah Menengah Pertama Negeri 5 Malang yaitu adanya pojok baca di masing-masing kelas, penambahan jumlah buku, adanya club baca 30 menit, dan hasil produk Gerakan Literasi Sekolah.Kata Kunci: Gerakan Literasi Sekolah, Tahap Pembiasaan, Tahap Pengembangan,  Pembelajaran